Diabetes control is worse in children and young people with type 1 diabetes requiring interpreter support - Jan Idkowiak; Jan Idkowiak; Jan Idkowiak; Suma Uday; Suma Uday; Suma Uday; Sabba Elhag; Sabba Elhag; Timothy Barrett; Timothy Barrett; Timothy Barrett; Renuka Dias; et al. (Frontiers in Clinical Diabetes and Healthcare, 2023)
IntroductionLanguage barriers can pose a significant hurdle to successfully educating children and young people with type 1 diabetes (CYPD) and their families, potentially influencing their glycaemic control.MethodsRetrospective case-control study assessing HbA1c values at 0, 3, 6, 9, 12 and 18 months post-diagnosis in 41 CYPD requiring interpreter support (INT) and 100 age-, sex- and mode-of-therapy-matched CYPD not requiring interpreter support (CTR) in our multi-diverse tertiary diabetes centre. Data were captured between 2009-2016. English indices of deprivation for each cohort are reported based on the UK 2015 census data.ResultsThe main languages spoken were Somali (27%), Urdu (19.5%), Romanian (17%) and Arabic (12%), but also Polish, Hindi, Tigrinya, Portuguese, Bengali and sign language. Overall deprivation was worse in the INT group according to the Index of Multiple Deprivation (IMD [median]: INT 1.642; CTR 3.741; p=0.001). The median HbA1c was higher at diagnosis in the CTR group (9.95% [85.2 mmol/mol] versus 9.0% [74.9 mmol/mol], p=0.046) but was higher in the INT group subsequently: the median HbA1c at 18 months post diagnosis was 8.3% (67.2 mmol/mol; INT) versus 7.9% (62.8 mmol/mol; CTR) (p=0.014). There was no hospitalisation secondary to diabetes-related complications in either cohorts.Summary and conclusionsGlycaemic control is worse in CYPD with language barriers. These subset of patients also come from the most deprived areas which adds to the disadvantage. Health care providers should offer tailored support for CYP/families with language barriers, including provision of diabetes-specific training for interpreters, and explore additional factors contributing to poor glycaemic control. The findings of this study suggest that poor health outcomes in CYPD with language barriers is multifactorial and warrants a multi-dimensional management approach.